Current advances in the diagnosis and management of gastroesophageal reflux disease - Shu-Wei Liang; Ming-Wun Wong; Chih-Hsun Yi; Tso-Tsai Liu; Wei-Yi Lei; Jui-Sheng Hung; Lin Lin; Benjamin D Rogers; Chien-Lin Chen (Tzu Chi Medical Journal)
Gastroesophageal reflux disease (GERD) is very common and defined as troublesome symptoms owing to excessive acid reflux. The spectrum of GERD is broad, including not only erosive esophagitis and Barrett's esophagus but also nonerosive reflux disease (NERD), reflux hypersensitivity, and functional heartburn. Patients with reflux symptoms despite normal endoscopy remain common clinical presentation, can be heterogeneous overlapping with functional gastrointestinal disorders. Ambulatory esophageal pH monitoring with and without impedance helps the diagnosis of NERD. Metrics such as baseline impedance and postreflux swallow induced peristaltic wave enhance diagnostic accuracy in patients with inconclusive diagnoses. The major treatment of all manifestations of GERD is acid suppression with proton pump inhibitors, while other therapies, such as reflux-reducing agents and adjunctive medications, can be individualized where the response to traditional management is incomplete. GERD patients often need long-term treatment due to frequent relapses. Anti-reflux surgery can be effective too. Endoscopic therapies have some promising results, but long-term outcomes remain to be determined.